Ionic transport through a composite structure of N-ethyl-N-methylpyrrolidinium tetrafluoroborate organic ionic plastic crystals reinforced with polymer nanofibres1. Issue 11 (21st March 2015) - Iranipour, N.; Gunzelmann, D. J.; Seeber, A.; Vongsvivut, J.; Doherty, C.; Ponzio, F.; O'Dell, L. A.; Hollenkamp, A. F.; Forsyth, M.; Howlett, P. C.
<x xml:space="preserve">Abstract</x> Composite plastic crystal electrolytes are shown to exhibit enhanced ion transport due to release of Li+ from a second phase into a solid solution.